2006
DOI: 10.1080/19485565.2006.9989124
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in disability life expectancy in us birth cohorts: The influence of sex and race

Abstract: Racial and sex disparities in chronic diseases and mortality are sources of health inequality and have been observed from infancy to adulthood. Disparities in health and mortality contribute to corresponding disparities in healthy life. I address two previously unanswered questions in the aging literature. First, does the racial and sex gap in healthy life narrow, persist, or expand over age and time, particularly considering severity of ill health, among the oldest old? Second, do some race-sex groups of birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…In contrast, Ferraro et al (1997) found widening racial disparities in self-assessed health. Soneji (2006) concluded cohort patterns in racial disparities in healthy life expectancy may depend on the severity level of disability, which is consistent with Manton’s hypothesis of dynamic equilibrium.…”
Section: Healthy Life Expectancy In the Past And Presentsupporting
confidence: 85%
“…In contrast, Ferraro et al (1997) found widening racial disparities in self-assessed health. Soneji (2006) concluded cohort patterns in racial disparities in healthy life expectancy may depend on the severity level of disability, which is consistent with Manton’s hypothesis of dynamic equilibrium.…”
Section: Healthy Life Expectancy In the Past And Presentsupporting
confidence: 85%
“…Our analytical approach centers on measuring changes in healthy longevity from a cohort perspective. This approach builds on both foundational work on the connections between period and cohort measures of disability-free life expectancy (DFLE) (e.g., Manton et al, 2008 ; Manton & Land, 2000 ; Soneji, 2006 ) and recent work exploring cohort changes in disability, chronic diseases, and health in the United States (e.g., Beltrán-Sánchez et al, 2016 ; Crimmins et al, 2019 ; Payne, 2022 ). A cohort perspective on healthy longevity more closely represents the lived experience of individuals within the population, allowing us to measure whether a change in healthy longevity (i.e., a compression of morbidity) is being experienced by an actual group of individuals in the population.…”
Section: Theoretical Frameworkmentioning
confidence: 99%